Gale encyclopedia of world history governments. - Gale Group (Detroit, Michigan Gale, 2008)
Provides a broad overview of national governments throughout history, explaining their structures and histories, key players and events, and how governments effect, and are affected by, social change.
Electronic reproduction.
Keywords: World politics -- Encyclopedias; World history -- Encyclopedias; Political science -- Encyclopedias; Electronic books